IMPROVE OF OVERHEAD POWER LINES MAGNETIC FIELD MITIGATION EFFICIENCY BY COMBINED ACTIVE AND PASSIVE CONTOURS SHIELDING - Б.І. Кузнецов; Т.Б. Нікітіна; І.В. Бовдуй; К.В. Чуніхін; В.В. Коломієць; Б.Б. Кобилянський (Технічна електродинаміка)
Problem of improving of efficiency of overhead power lines magnetic field mitigation by combined active and passive contours shielding and reducing system sensitivity to uncertainty and changes in system parameters considered. Design of combined active and passive shielding reduced to solving the geometric inverse problem of magneto-quasi-static’s based on vector game solution with vector payoff calculated based on Maxwell equations solution in a quasi-stationary approximation using COMSOL Multiphysics software. Vector game solution calculated based on particles multi-swarm optimization algorithms from Pareto optimal solutions set taking into account binary preference relations. During design of combined active and passive shielding number and spatial arrangement coordinates of active compensating windings and passive contours, as well as currents and phases in active compensating windings calculated. The computer simulation and experimental research of combined active and passive contours shielding for improving of overhead power lines magnetic field mitigation efficiency presented. References 3, figures 2.